U.S. pivots to maritime Southeast Asia - Ristian Atriandi Supriyanto (2012)
The United States decision to deploy littoral combat ships in Singapore signals a maritime focus in its pivot to the Asia-Pacific. It reaffirms U.S. commitment to support Southeast Asian allies and partners amid China’s growing maritime assertiveness in the region.